Elasticity theory, applications, and numerics - Sadd, Martin H. (Martin Howard) (Amsterdam ; Boston : Elsevier Butterworth Heinemann, 2005)
Although there are several books in print dealing with elasticity, many focus on specialized topics such as mathematical foundations, anisotropic materials, two-dimensional problems, thermoelasticity, non-linear theory, etc. As such they are not appropriate candidates for a general textbook. This book provides a concise and organized presentation and development of general theory of elasticity. Complemented by a Solutions Manual and including MatLab codes and coding, this text is an excellent book teaching guide. - Contains exercises for student engagement as well as the integration and use of MATLAB Software - Provides development of common solution methodologies and a systematic review of analytical solutions useful in applications of engineering interest - Presents applications of contemporary interest.
Mathematical Preliminaries, Deformation: Displacements and Strains, Stress and Equilibrium, Material Behavior-Constitutive Equations, Formulation and Solution Strategies, Strain Energy and Related Principles, Two-Dimensional Formulations, Two-Dimensional Problem Solution, Saint -- Venant Extension, Torsion and Flexure, Complex Variable Methods, Anisotropic Elasticity, Thermoelasticity, Displacement Potentials and Stress Functions, Micromechanics Applications, Numerical Methods: Finite and Boundary Element Methods, Appendices A-D.
Includes bibliographical references and index.
Keywords: Elasticity; Electronic books